TATA KELOLA PEMILU : KASUS PENATAAN DAERAH PEMILIHAN PADA PEMILU 2024 DI KOTA PEKANBARU - Frimusdya, Sasky; ', Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
In this research, there are phenomena, including the increase in the population of Pekanbaru City, so that the arrangement of electoral districts shows an increase in the number of seat allocations for the first time. The formation of electoral districts has the main objective of strengthening political representation and achieving proportionality in accordance with geographical coverage, administrative structure and political dynamics. From this phenomenon, the aim of this research is to describe and find out how election governance is: the case of electoral district structuring in the 2024 election in Pekanbaru City. The research method used is a qualitative method with descriptive explanation. The type of research data used is primary data obtained from research informants and secondary data, namely supporting data such as related documents that can support data for research. Data collection techniques were carried out by means of interviews and documentation. The research location is in Pekanbaru City. The results of this research found that in structuring electoral districts in Pekanbaru City there are three variables that determine success in Election Governance, namely: 1) Rule Making. At this stage of the process, the Pekanbaru City KPU has determined the number of seat allocations according to existing rules, namely by observing the data provided. There is. In this stage, the Pekanbaru City KPU succeeded in providing 2 drafts to be submitted for public examination. And for design 3, an opportunity will be given to stakeholder elements to negotiate regarding the design that will be made; 2) Rule Application Pekanbaru City KPU carried out public test activities which were quite fierce, inviting pros and cons, especially between political parties because small political parties were not yet prepared for the competition for seats with the splitting of electoral districts; and 3) Rule Adjudication in the form of supervision carried out by the Riau Province KPU and the Republic of Indonesia KPU in the arrangement of electoral districts carried out by the Pekanbaru City KPU. The Indonesian KPU decided that the design used was design 3 for the arrangement of the 2024 election electoral districts. Keywords: Election Governance, Arrangement, Electoral District.